Empirical study of Black-Scholes warrant pricing model on the stock exchange of Singapore. - Leow, Soon Siong. (2009)
The pricing of warrants is a relatively new subject in securities research in Singapore. Warrant is basically a security which gives its owner the right to exchange for a fixed number of shares of a specified common stock at fixed price at any time on or before the expiration date. Unlike options, exercise of warrants will result in increasing the number of stocks outstanding, thus causing a dilution in the price of the underlying stock. In 1973, Fischer Black and Myron Scholes presented one of the first equilibrium option pricing models. Since then, a large number of studies have been done on both options as well as warrants prices. However, it is in the early 80's that warrants became popular in Singapore. A few studies have been made but it is still an instru-ment not much understood by the investors and the public.